Community and data integration approach using requirement centric operational data store model (ReCODS-Model) for business intelligence applications - Abu Bakar, Muhamad Shahbani; Shiratuddin, Norshuhada (World Scientific and Engineering Academy and Society (WSEAS), 2009)
Building a Business Intelligence (BI) application is very challenging as it is a young discipline and does not yet offer well-established strategies and techniques for the developments process when compared to the software engineering discipline. Furthermore, information requirements analysis for BI applications which integrate data from heterogeneous sources differs significantly from requirements analysis for a conventional information system. Requirement Centric Operational Data Store Model (ReCODS-M) to build BI application that focuses on operational information to support business operations is proposed. In this model, combination of community interaction and data integration approach were used to identify the requirements for developing BI application. Furthermore, how the operational data store can be used for operational and tactical information and can be transferred to a data warehouse for supporting analytical information and decision making is also presented. Finally, to verify and validate the proposed model, the case study approach using web application development in selected subject areas is elaborated.